2021
DOI: 10.1111/gcb.15626
|View full text |Cite
|
Sign up to set email alerts
|

The ecological impacts of multiple environmental stressors on coastal biofilm bacteria

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Ocean acidification (OA) and warming (OW), alone or in combination, did not significantly affect alpha diversity nor composition of microbial communities on the shell surface of blue mussels. Such a low compositional and structural susceptibility of biofilm communities to OA, OW, and climate change (CC) is surprising since several studies have reported that bacterioplankton communities (Lindh et al, 2013;Wang et al, 2021), bacterial consortia on living (Mensch et al, 2020(Mensch et al, , 2016 and inert surfaces (Ferguson et al, 2021) are sensitive to these stressors, notably OW. The blue mussel inhabits coastal areas and microbes on their shell might thus be able to withstand environmental changes projected for the end of the 21 st century.…”
Section: Compositional and Structural Responses Of Microbial Communit...mentioning
confidence: 99%
“…Ocean acidification (OA) and warming (OW), alone or in combination, did not significantly affect alpha diversity nor composition of microbial communities on the shell surface of blue mussels. Such a low compositional and structural susceptibility of biofilm communities to OA, OW, and climate change (CC) is surprising since several studies have reported that bacterioplankton communities (Lindh et al, 2013;Wang et al, 2021), bacterial consortia on living (Mensch et al, 2020(Mensch et al, , 2016 and inert surfaces (Ferguson et al, 2021) are sensitive to these stressors, notably OW. The blue mussel inhabits coastal areas and microbes on their shell might thus be able to withstand environmental changes projected for the end of the 21 st century.…”
Section: Compositional and Structural Responses Of Microbial Communit...mentioning
confidence: 99%
“…Biofilms and other bacteria aggregate systems are collectives of bacteria that are typically surface bound and self-encased in an extracellular polymeric substance (EPS) matrix. , Biofilms can have beneficial effects on ecosystems such as soil and coastal environments, contributing to nutrient cycling and carbon balance. The resilience of multicellular bacterial biofilms, both in development and response to environmental stressors, has deleterious effects in medicine and engineering, contributing to microbial infections , and biofouling of water ways and industrial machinery .…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms and other bacteria aggregate systems are collectives of bacteria that are typically surface bound and self-encased in an extracellular polymeric substance (EPS) matrix [3, 4]. Biofilms can have beneficial effects on ecosystems such as soil [5] and coastal environments [6], contributing to nutrient cycling and carbon balance. The resilience of multicellular bacterial biofilms, both in development and response to environmental stressors, has deleterious effects in medicine and engineering, contributing to microbial infections [7, 8] and biofouling of water ways and industrial machinery [9].…”
Section: Introductionmentioning
confidence: 99%